Estimates of Lp Modulus of Continuity of Generalized Bounded Variation Classes - Heping Wang; Zhaoyang Wu (Journal of Function Spaces)
Some sharp estimates of the Lp1≤p<∞ modulus of continuity of classes of Λφ-bounded variation are obtained. As direct applications, we obtain estimates of order of Fourier coefficients of functions of Λφ-bounded variation, and we also characterize some sufficient and necessary conditions for the embedding relations Hpω⊂ΛφBV. Our results include the corresponding known results of the class ΛBV as a special case.